2017
DOI: 10.1071/ah16032
|View full text |Cite
|
Sign up to set email alerts
|

Subsidies to target specialist outreach services into more remote locations: a national cross-sectional study

Abstract: Objective. Targeting rural outreach services to areas of highest relative need is challenging because of the higher costs it imposes on health workers to travel longer distances. This paper studied whether subsidies have the potential to support the provision of specialist outreach services into more remote locations.Methods. National data about subsidies for medical specialist outreach providers as part of the Wave 7 Medicine in Australia: Balancing Employment and Life (MABEL) Survey in 2014.Results. Nearly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In Australia, a national policy subsidises travel costs for 20% of all specialist outreach workers. Those supported by this are more likely to be specialists in fields related to national rural health priority areas and to visit more remote locations [44, 45].…”
Section: Findings From Mabelmentioning
confidence: 99%
“…In Australia, a national policy subsidises travel costs for 20% of all specialist outreach workers. Those supported by this are more likely to be specialists in fields related to national rural health priority areas and to visit more remote locations [44, 45].…”
Section: Findings From Mabelmentioning
confidence: 99%
“…This suggests that there may be cost implications related to specialists self‐funding their travel costs and absorbing the costs of travel time, which are likely to increase as specialists travel to more distant or hard to reach communities. We found that subsidies, whether provided to outreach specialists from the RHOF or another source, increased the rate of more remote area services by up to 4.4 times 16 . Additionally, RHOF subsidies relate to more regular outreach services in remote locations, with 62% of these specialists intending to continue for 5 or more years.…”
mentioning
confidence: 82%
“…About half of the specialists undertake outreach work without any support from subsidies, with the remainder supported by the RHOF (19%) or other types of subsidies (27%). This suggests that specialists incur some personal costs of time and travel for outreach participation, although 33% of non‐subsidised providers work publicly, potentially covered by salaried arrangements 16 …”
mentioning
confidence: 99%
See 2 more Smart Citations